Framework Administered Account for Select Fund Activities : The Republic of South Sudan Macroeconomic Capacity Building. (Policy Papers; Policy Paper ;, 2012)
In March 2009, the Fund established a new Framework Administered Account to administer external financial resources for Selected Fund Activities (the 'SFA Instrument'). The financing of activities under the terms of the SFA Instrument is implemented through the establishment and operation of a subaccount within the SFA. This paper requests Executive Board approval to establish the Republic of South Sudan Macroeconomic Capacity Building Subaccount (the 'Subaccount') under the terms of the SFA Instrument.